A new revised M-Of-K Run Rules Method in X-Bar control chart for estimated parameters. - Teh, Sin Yin (Universiti Sains Malaysia, 2016)
Good knowledge and understanding of the behaviour of the control chart with estimated process parameters is very essential to engineers. Since the run length distribution is highly right-skewed and the skewness changes with designed parameters, average run length does not provide a complete understanding about the performance of the control chart with estimated process parameters.